-12(k+4)=16

Simple and best practice solution for -12(k+4)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12(k+4)=16 equation:


Simplifying
-12(k + 4) = 16

Reorder the terms:
-12(4 + k) = 16
(4 * -12 + k * -12) = 16
(-48 + -12k) = 16

Solving
-48 + -12k = 16

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + -12k = 16 + 48

Combine like terms: -48 + 48 = 0
0 + -12k = 16 + 48
-12k = 16 + 48

Combine like terms: 16 + 48 = 64
-12k = 64

Divide each side by '-12'.
k = -5.333333333

Simplifying
k = -5.333333333

See similar equations:

| 1=-4-7n+2n | | 6x+4=148 | | 7p-5=1+5p+3p | | 10x=5.25 | | 6d+12=d+12 | | 5=1(-1)+b | | 17x+4=9x+12 | | 30-x+50=60 | | -3+6c=17 | | 15x+3(x+4)=-6 | | 3(2x+4)=2x-20 | | 25c^2-16p^2= | | 3h+24=-12 | | (5x-2)3=24 | | 9y-7+2(3y+5)=-3(y+1) | | 3x-11=-2x-1 | | 6.4y=5.2 | | 6(2/3g+1/2g)=14 | | -7x+28=14 | | 120+48x-16x^2=0 | | -6x-13+8x-23=-4 | | .666666(-6+9x)+16=20 | | 121r-8-12= | | -6x^2+18x=12 | | -540+13.20x=1500 | | -5(-5)+9(-5)= | | T-4(t-3)=4+(3t+6) | | 5x+3(x-2)+5.5(x+9)=0 | | 8x^2+3=-90 | | 18-9.8x= | | 14+y=4 | | 4x-6x+174=10x+90 |

Equations solver categories